The relationship between cognitive function and depression severity in multiple sclerosis patients: Application of the Brief Repeatable Battery of Neuropsychological Tests (BRBNT) in Lithuania - Grambaitė, Ramunė; Sargautytė, Rūta (Psichologija, 2005)
Multiple sclerosis (MS) is an inflammatory and neurodegenerative disorder that affects primarily the cerebral white matter, thereby causing both physical and psychological disability. The purpose of this study was to investigate the possible relationship between cognitive function and depression severity in MS patients, as well as sensitivity and specificity characteristics of the BRBNT (The Brief Repeatable Battery of Neuropsychological Tests). We investigated 41 MS patients and 52 healthy people. Forty-one controls were selected from fifty-two healthy subjects and were individually matched with MS subjects for age, gender and education. BRBNT (Rao and Peyser, 1986) was designed for measuring verbal learning, visuospatial learning, sustained attention and concentration, information processing speed and verbal fluency cognitive functions. The B version of the BRBNT was translated and used in our study. Beck Depression Inventory-Second Edition (BDI-II) (Beck, 1996) was used for the evaluation of depression severity. Results of our study confirmed that depression severity was associated with verbal learning: Consistent Long Term Retrieval and the Delayed Recall significantly negatively related to depression severity. The relationship between information processing speed and depression severity was also negative, but not statistically significant. The five individual BRBNT tests separately did not significantly discriminate healthy controls from MS patients; however, when all the five BRBNT tests put together we found 100% sensitivity of and 100% specificity. Our findings lead to the conclusion that neuropsychological testing is important in organizing help strategies for MS patients. BRBNT is a sensitive measure of cognitive function in MS, and may assist with differential diagnosis. Similarly, BRBNT could well be applied to other groups of patients, whose illness results in physical and/or cognitive functional limitations.